A HMM-based method for anomaly detection - Fei Wang; Hongliang Zhu; Bin Tian; Yang Xin; Xinxin Niu; Yu Yang (2011 4th IEEE International Conference on Broadband Network and Multimedia Technology, 2011)
Intrusion-detection systems (IDSs) are essential tools for the security of computer systems. Anomaly detection, which uses knowledge about normal behaviors and attempts to detect intrusions by noting significant deviations, has been paid more and more attention. In this paper, we introduce a HMM-based method for anomaly detection. The proposed method is composed of two important stages: off-line training stage and on-line testing stage. In the off-line training stage, we train the normal behaviors by hidden Markov models (HMMs). In the on-line testing stage, we make the final decision based on the minimum risk Bayesian decision theory. We deploy the method on an IDS system to evaluate its performance, and the experimental results demonstrate that our method can achieve satisfying results.